Postpartum anaemia in three New Zealand district health board regions: An observational study of incidence and management. (18th July 2022) - Calje, Esther; Marriott, Joy; Oyston, Charlotte; Dixon, Lesley; Bloomfield, Frank; Groom, Katie
Abstract : Background: The incidence of postpartum anaemia (PPA) in New Zealand, and the extent of intravenous iron (IV‐iron) use in its treatment, are unknown. Aims: To report the incidence of PPA in three district health board (DHB) regions and describe current management of moderate to severe PPA, including by ethnicity. Materials and Methods: Retrospective observational study of PPA (haemoglobin (Hb) <100 g/L) in three DHBs from July–December 2019. Cases with moderate to severe PPA (Hb <90 g/L) were reviewed and management compared to local and national guidance. Logistic regression examined demographic associations of PPA. Results: There were 8849 women who gave birth during the study period: 4076 (46%) had postpartum Hb testing and 1544 (38%) had PPA. Of those tested, and after adjusting for deprivation and region, European women had lower adjusted odds ratios compared to Māori for being identified as having PPA (0.46, 95% CI 0.37–0.57, P < 0.01). Of 681 women with Hb <90 g/L, 278 (41%) received IV‐iron only, 66 (10%) red blood cell transfusion (RBC‐T) only and 155 (23%) both. Of those receiving RBC‐T, 40/221 (18%) were actively bleeding. Māori (92/138, 67%) and Pacific (127/188, 68%) women with Hb <90 g/L had the highest incidence of IV‐iron use. No guidelines provided recommendations for haemodynamically stable women without active bleeding. Conclusion: The incidence and management of PPA differs by ethnicity but fewer than half of the women had Hb testing, making precise determination of incidence impossible. The majority of women with Hb <90 g/L received IV‐iron, with or without RBC‐T.